Prevalence and correlates of physical bullying behaviours (on/off-school property) among adolescents in Saint Vincent and the Grenadines - Jacob Owusu Sarfo; Paul Obeng; Priscilla Y. A. Attafuah; Newton Isaac Gbordzoe; Crescens Osei Bonsu Ofori (BMC, 2024)
Abstract Background Bullying remains a serious public health and educational concern among school-going adolescents worldwide. However, no national survey has examined the prevalence and correlates of physical bullying (on and off-school property) among school-going adolescents in the Island country of Saint Vincent and the Grenadines. This study sought to examine the prevalence and correlates of physical bullying among adolescents from St. Vincent and the Grenadines. Methods We analysed data from the 2018 Global School-based Student Health Survey using Pearson Chi-square and Binomial Logistic Regression, with an adjusted odds ratio (AOR) at a 95% confidence interval (CI). Results Among this population, physical bullying on/off-school property was prevalent among 24% and 18%, respectively. After adjusting for other predictors, we found that males were less likely to be bullied on school property than females. However, being a younger adolescent (≤ 15 years old), being physically attacked, cyberbullied, having close friends, and having suicidal ideas were associated with increased odds of being physically bullied on school property. Also, being physically attacked, cyberbullied, worried, and having suicidal plans increased the odds of being physically bullied off school property. Conclusion We recommend a multidisciplinary approach to adolescent bullying prevention in Saint Vincent and the Grenadines and countries with similar characteristics based on our findings. Trail registration Global School-Based Student Health Survey 2018 (VCT_2018_GSHS_v01) Registered August 20, 2021, https://extranet.who.int/ncdsmicrodata/index.php/catalog/878.